INFRASTRUKTUR PUBLIK MENJADI DETERMINASI PENTING TERHADAP PENINGKATAN PENDAPATAN PERKAPITA (Studi Kasus Di Kabupaten Nganjuk) - Rony Kurniawan (Master of Public Administration, Universitas Slamet Riyadi, 2018)
Kurniawan, 2018. “Public infrastructure is an important determinant forincreasing per capita income in certain areas”. Economic Science,Universitas Nusantara PGRI Kediri.The purpose of this research is to know the existence of publicinfrastructure, that is, electricity infrastructure of drinking water consumerand transportation (long way) is important determination to influenceincome per capita. Partially through t-test of three pairs of variables of thisstudy, that is the net water variable (X2) has no correlation to the increaseof income per capita in Nganjuk regency. The results rejected previousresearch by Nuritasari (2013), Muhammad & Sari, Diana (2015) andValeriani (2016). While variable of electricity customer (X1) and length ofroad (X3) become important determination to change of income percapita. The results support previous research conducted by Nuritasari(2013), Muhammad & Sari, Diana (2015), Valeriani (2016).However, simultaneously (F test) that public infrastructure ie electricitycustomer (X1), clean water subscriber (X2) and road length (X3)significantly affect the change of income per capita (Y). Researchers usesaturated sample data or all time series data from 2000-2016 collectedfrom the Central Bureau of Statistics (BPS) Nganjuk. Researchers useEview's data version 8 to get statistical value so that this research can bedone in accordance with the purpose of research.Keywords: Public Infrastructure, Per Capita Income, Nganjuk District